Psychometric Properties of the Norwegian Version of the Fear of COVID-19 Scale. - Iversen, M. M.; Norekvål, T. M.; Oterhals, K.; Fadnes, L. T.; Mæland, S.; Pakpour, A. H.; Breivik, K. (International Journal of Mental Health & Addiction, 2022)
To examine the psychometric properties of the Norwegian version of the Fear of COVID-19 Scale (FCV-19S), randomly selected individuals from a larger registry study were invited. We assessed the reliability and validity of the instrument in a sample of 1089 adults in Norway (response rate 73%). Internal consistency measured by Cronbach's alpha (0.88) was acceptable. Omega alphaHierarchical (ωt = 0.69) was lower indicating that the general factor is less reliable, explaining 69% of the total variance. Confirmatory factor analysis indicated that the FCV-19S is not strictly unidimensional. Exploratory graph analysis and confirmatory factor analysis supported a two-factor model (cognitive and somatic fear), which were highly correlated (r = 0.84). The Norwegian version of the FCV-19S showed an underlying two-factor structure. However, the high correlation means the two latent factors (cognitive and somatic fear) act as indicators for a second-order general factor and support use of the FCV-19S sum score. The FCV-19S appears to be a valid instrument to assess fear of COVID-19 with good psychometric properties.